Conselho Nacional de Justiça: Desenho Institucional, Construção de Agenda e Processo Decisório - Roberto Fragale Filho (Universidade do Estado do Rio de Janeiro, 2013)
After four administrations, a recent analysis of the work by the Brazilian National Council of Justice concludes that the glass dome has cracked, since the inertia has been broken and taboos have been challenged, thereby injecting new energy into the judiciary systems leading role through its integration into the public arena. This break developed from an institutional design built under Constitutional Amendment 45/2004, which assigns an external oversight role to the Council, the contours of which have been constructed through its agenda-building, the composition of its membership, and the possibilities in its decision-m aking process. These three dimensions help explain the Councils role in the current architecture of the Brazilian judiciary and shed light on the debates over its scope of action.